A modified supraclavicular artery island flap for reconstruction of oral and maxillofacial defects - Wang, Ruiyu; Shao, Tingru; Liu, Chundong; Zhang, Xiaogen; Lv, Xiaozhi (Oral surgery, oral medicine, oral pathology and oral radiology, 2024)
To overcome the limitation of the supraclavicular artery island flap (SCAIF), we describe a modified SCAIF which incorporates a portion of the upper trapezius and the superficial branch of the transverse cervical artery (TCA) for the reconstruction of oral and maxillofacial defects. The modified SCAIF was used on 20 patients at our hospital between April 2013 and August 2022. All patients underwent resection of the primary lesion site and immediate reconstruction with the modified SCAIF. Demographic data and flap details were recorded. Complications were assessed for at least a 6-month follow-up period. This study included 20 patients. The mean flap harvest time was 50 minutes. The mean flap length was 6.0 cm, and the mean flap width was 5.0 cm. All flaps of 20 cases survived with good appearance, and no shoulder morbidity was found during a follow-up period of at least 6 months. The modified SCAIF is a versatile and reliable local flap option for moderate to large reconstruction in this special region after resection of the primary lesions. We found this simple flap design has overcome the limitations of the traditional one with a reliable blood supply and adequate tissue for larger defects.